2021
DOI: 10.48550/arxiv.2112.09523
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cosmological bounce and the cosmological constant problem

Abstract: We demonstrate that the famous cosmological constant problem of the standard cosmology naturally vanishes in the suitable model-independent effective approach towards quantum gravity, while also studying the effect of quantum space-time fluctuations on the cosmological evolution. We start from the general list of assumptions required for a consistent and complete model of the Universe, which replaces the big bang singularity with a bounce, and thus invokes a modification of the classical field equations for gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…A variety of studies bear relation in different ways with these investigations, see e.g. [63][64][65][66][67][68][69][70][71][72][73][74][75][76] and corresponding references. However, it was only recently, in the aforementioned work [57], where an explicit form of the RVM vacuum density could be derived within the QFT context.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of studies bear relation in different ways with these investigations, see e.g. [63][64][65][66][67][68][69][70][71][72][73][74][75][76] and corresponding references. However, it was only recently, in the aforementioned work [57], where an explicit form of the RVM vacuum density could be derived within the QFT context.…”
Section: Introductionmentioning
confidence: 99%
“…It was also demonstrated that the problem of magnetogenesis has a simple possible solution in the model-independent approach to bouncing cosmology [38]. Recently, we proposed a model-independent approach to bouncing cosmology in which we proposed a simple solution of the cosmological constant problem and also studied the effects of quantum fluctuations of the spacetime geometry [39]. We will use some of the obtained conclusion in the present study of wormholes created during the cosmological bounce.…”
Section: Introductionmentioning
confidence: 87%
“…model independent) description of bouncing cosmological solutions. Here we follow the steps discussed in [39]. With this aim we introduce the following action for gravity (c = 1):…”
Section: General Approach To Bouncing Cosmologymentioning
confidence: 99%
See 2 more Smart Citations